Endless forms : the secret world of wasps - Sumner, Seirian (Harper, an imprint of HarperCollins Publishers, 2022)
In this eye-opening and entertaining work of popular science in the spirit of The Mosquito, Entangled Life, and The Book of Eels, a leading behavioral ecologist transforms our understanding of wasps, exploring these much-maligned insects' secret world, their incredible diversity and complex social lives, and revealing how they hold our fragile ecosystem in balance.